2005
DOI: 10.1016/j.polymer.2005.07.093
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical properties of azobenzene-containing poly(1-alkyne)s with different spacer lengths and ring substituents

Abstract: Poly(1-alkyne)s containing azobenzene pendants with different spacer lengths and ring substitutents-{HCaC[(CH 2) m COO-C 6 H 4-NaN-C 6 H 4-NO 2 ]} n-P1(m) mZ3, 8 and-{HCaC[(CH 2) m COO-C 6 H 3-o-Br-NaN-C 6 H 4-NO 2 ]} n-P2(m) mZ3, 8} are designed and synthesized. The polymers are prepared in satisfactory yields with high molecular weights (M w up to 3.3!10 4 Da) by [Rh(nbd)Cl] 2-Et 3 N in THF or dioxane. Their structures and properties are characterized and evaluated by IR, UV, NMR, TGA, nonlinear optical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…On the contrary, the threshold increased from 0.17 to 0.29 mJ/cm 2 when linear transmittance was increased to 75% (c ¼ 0.036 mg/mL). Similar results were also found by Kojima Y and our previous publications (5,25). It is the reason that the solution with a higher concentration has more molecules per unit volume, which should absorb the energy of the harsh laser more efficiently.…”
Section: Optical Limiting Mechanism Of the Polyurethanessupporting
confidence: 89%
See 1 more Smart Citation
“…On the contrary, the threshold increased from 0.17 to 0.29 mJ/cm 2 when linear transmittance was increased to 75% (c ¼ 0.036 mg/mL). Similar results were also found by Kojima Y and our previous publications (5,25). It is the reason that the solution with a higher concentration has more molecules per unit volume, which should absorb the energy of the harsh laser more efficiently.…”
Section: Optical Limiting Mechanism Of the Polyurethanessupporting
confidence: 89%
“…Among the organic materials, some NLO polymers are considered to be promising materials, mainly because they offer many advantages such as good optical limiting properties, a high optical damage threshold, fast time response, and good processability to form optical devices (2)(3)(4)(5)(6).…”
Section: Preparation and Optical Limiting Properties Of Polyurethane mentioning
confidence: 99%
“…Incorporating such a chromophore into PAs might offer materials with novel optical properties. We synthesized a series of PAs with NLO properties [76][77][78][79][80]. Fullerenes are known to limit intense optical pulses via a reverse saturable absorption mechanism.…”
Section: Optical Nonlinearitymentioning
confidence: 99%
“…17 shows the optical limiting properties of the polymers 70 and 71 with azobenzene as the pendant at the same linear transmittance (T = 75%)[76]. All the polymers are good optical limiters, especially for those with short spacer lengths.For example, the limiting threshold and limiting amplitude of 70(3) are 0.245 and 0.349 J cm −2 , respectively, which are 1.3 and 1.2 times lower than those of 70(8).…”
mentioning
confidence: 97%
“…Usually, the anisotropic interactions between the mesogenic groups give rise to the observation of liquid‐crystalline behavior, whereas the flexible spacer decouples the opposing tendencies of the liquid‐crystal groups to self‐assemble from those of the polymer backbones to adopt random coil conformations. Systematic studies on the structure–property relationship of the azo‐containing side‐chain LCPs have also revealed that phase transition behaviors are strongly dependent on them . For example, García et al have studied the phase behaviors of liquid‐crystalline polymers bearing phenylene(azobenzene) moieties substituted with an electron‐donor or electron‐acceptor lateral group.…”
Section: Introductionmentioning
confidence: 99%